Crenças e práticas de professores de língua inglesa participantes do programa gira mundo: uma abordagem sob a ótica da política linguística - Ferreira, Janaína (2020)
The Gira Mundo International Exchange Program carried out by the Paraíba State government aims not only at the qualification of teachers and students, but also at the evolution of the education system through the application of successful experiences in countries that stand out in the educational segment. In this sense, given the importance of this program in the educational context of the State, this work aims to investigate beliefs and teaching practices of English language teachers participating in the Gira Mundo Program in Finland. For this, we adopted the language policy perspective developed by Spolsky (2004, 2009, 2012), which understands beliefs as valuations about languages, and by Shohamy (2006), who conceives the mechanisms of language policy as devices, of an implicit or explicit nature, that create, perpetuate and affect the ideologies and practices about languages that are in force in a given society. Methodologically, it is a qualitative interpretative research (BORTONI-RICARDO, 2008), carried out based on semi-structured interviews with four English language teachers. It were used contributions from Textual Linguistics and Argumentative Semantics (KOCH, 2011, 2015) for data analysis. The findings showed that teachers have the following beliefs: the importance of English in the world; the possibility of learning English without visiting or living in the country of that language proved to be variable, since learning is conditioned to “self-education” and “motivation”, constituting a “longer path” for learning; the requirement of English in basic education, but also the importance of the presence of other foreign languages in the curriculum; the possibility of learning English at school, although it is easier in private institutions; the “motivation” and contact with the language with both natives and non-natives as the “secret” for learning English; and English is not difficult, but some elements can be difficult, such as syntax and phonetics. Regarding teaching practices, everyone said that there is no longer the issue of preferred variety of English language, however the American and British are present in the classroom, as these are the ones that the teachers learned. We emphasize that the GMF caused changes in their teaching practices, leading teachers to prioritize communication, internet, student’s role and the deconstruction of beliefs on part of the students and to use active methodologies and digital tools. This research seeks to contribute to foster studies on the impacts of public educational policies and language policies on the continuing education of language teachers.